Does the scarcity of urban space resources make the quality of underground space planning more sustainable? A case study of 40 urban underground space master plans in China - Zhang, Mingdi; Xie, Ziang; He, Lei (Frontiers in Environmental Science, 2022)
The international community has reached a consensus on promoting the sustainable development of global cities. As an important and irreversible space resource in a city, the development and utilization of urban underground space should follow the principle of sustainability and emphasize scientific and forward-looking planning. At present, most cities have formulated urban underground space master plans. However, due to the lack of an effective evaluation method, the plan quality is uneven, which directly affects the sustainability of underground space development and utilization. This paper proposes a set of sustainability evaluation framework of underground space planning based on relevant planning standards and plan quality evaluation protocol, and makes a comparative analysis of the 40 urban underground space master plans formulated in China from 2004 to 2020. The research found that the planning documents generally reflected the problem of emphasizing design strategies and engineering technology while neglecting implementation and humanistic care; administrative region, population density, land price and other variables closely related to the scarcity of urban space resources are the main factors affecting the quality of urban underground space planning. The conclusions of this paper can aid planners and researchers to identify the problems and influencing factors of underground space planning related to sustainability, and summarize the methods to improve the quality of underground space planning.